Environment, Leptin Sensitivity, and Hypothalamic Plasticity - Marco Mainardi; Tommaso Pizzorusso; Margherita Maffei (Neural Plasticity)
Regulation of feeding behavior has been a crucial step in the interplay between leptin and the arcuate nucleus of the hypothalamus (ARC). On one hand, the basic mechanisms regulating central and peripheral action of leptin are becoming increasingly clear. On the other hand, knowledge on how brain sensitivity to leptin can be modulated is only beginning to accumulate. This point is of paramount importance if one considers that pathologically obese subjects have high levels of plasmatic leptin. A possible strategy for exploring neural plasticity in the ARC is to act on environmental stimuli. This can be achieved with various protocols, namely, physical exercise, high-fat diet, caloric restriction, and environmental enrichment. Use of these protocols can, in turn, be exploited to isolate key molecules with translational potential. In the present review, we summarize present knowledge about the mechanisms of plasticity induced by the environment in the ARC. In addition, we also address the role of leptin in extrahypothalamic plasticity, in order to propose an integrated view of how a single diffusible factor can regulate diverse brain functions.